The Tunka-Grande scintillation array: Current results - A. L. Ivanova, I. Astapov, P. Bezyazeekov, E. Bonvech, A. Borodin, N. Budnev, A. Bulan, D. Chernov, A. Chiavassa, A. Dyachok, A. Gafarov, A. Garmash, V. Grebenyuk, E. Gress, O. Gress, T. Gress, A. Grinyuk, O. Grishin, A. D. Ivanova, N. Kalmykov, V. Kindin, S. Kiryuhin, R. Kokoulin, K. Kompaniets, E. Korosteleva, V. Kozhin, E. Kravchenko, A. Kryukov, L. Kuzmichev, A. Lagutin, M. Lavrova, Y. Lemeshev, B. Lubsandorzhiev, N. Lubsandorzhiev, A. Lukanov, D. Lukyantsev, S. Malakhov, R. Mirgazov, R. Monkhoev, E. Osipova, A. Pakhorukov, L. Pankov, A. Pan, A. Panov, A. Petrukhin, I. Poddubnyi, D. Podgrudkov, V. Poleschuk, V. Ponomareva, E. Popova, E. Postnikov, V. Prosin, V. Ptuskin, A. Pushnin, R. Raikin, A. Razumov, G. Rubtsov, E. Ryabov, Y. Sagan, V. Samoliga, A. Satyshev, A. Silaev, A. Silaev, A. Sidorenkov, A. Skurikhin, A. Sokolov, L. Sveshnikova, V. Tabolenko, L. Tkachev, A. Tanaev, M. Ternovoy, R. Togoo, N. Ushakov, A. Vaidyanathan, P. Volchugov, N. Volkov, D. Voronin, A. Zagorodnikov, D. Zhurov, I. Yashin (SciPost Physics Proceedings, 2023)
The Tunka-Grande experiment is a scintillation array with about 0.5 km$^2$ sensitive area at Tunka Valley, Siberia, for measuring charged particles and muons in extensive air showers (EASs). Tunka-Grande is optimized for cosmic ray studies in the energy range 10 PeV to about 1 EeV, where exploring the composition is of fundamental importance for understanding the transition from galactic to extragalactic origin of cosmic rays. This paper attempts to provide a synopsis of the current results of the experiment. In particular, the reconstruction of the all-particle energy spectrum in the range of 10 PeV to 1 EeV based on experimental data from four observation seasons is presented.